2022
DOI: 10.21608/znj.2022.245633
|View full text |Cite
|
Sign up to set email alerts
|

Academic Procrastination and Self-control of Faculty Nursing Students

Abstract: Background: Academic procrastination in university student is closely related to lower levels of self-control, self-efficacy, emotional intelligence and academic performance with increase in anxiety level. Aim of the study: was to assess the relationshipbetween Academic Procrastination, and self-control of Nursing Students at Faculty of Nursing -Zagazig University. Subjects and Methods: Research design: A descriptive design was utilized in this study. Setting: This study was conducted at Faculty of Nursing -Za… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Some literature also pinpointed that students’ majors also influenced procrastination tendencies. For instance, some studies found high levels of academic procrastination among nursing students and stated the possible reasons as course and assignment overload, varied experiences during practical clinical hours, and frequent evaluation that affected concentration and led to decreased coping and learning outcomes (Ghaffari et al, 2021 ; Ravanipour et al, 2015 ; Sabry Abd El-Salam et al, 2022 ). Upon agreement, some scholars believed that individuals procrastinate due to overwhelmed responsibilities that, in turn, cause emotional and behavioral problems (Balkis & Duru, 2009 ; Quinn, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some literature also pinpointed that students’ majors also influenced procrastination tendencies. For instance, some studies found high levels of academic procrastination among nursing students and stated the possible reasons as course and assignment overload, varied experiences during practical clinical hours, and frequent evaluation that affected concentration and led to decreased coping and learning outcomes (Ghaffari et al, 2021 ; Ravanipour et al, 2015 ; Sabry Abd El-Salam et al, 2022 ). Upon agreement, some scholars believed that individuals procrastinate due to overwhelmed responsibilities that, in turn, cause emotional and behavioral problems (Balkis & Duru, 2009 ; Quinn, 2019 ).…”
Section: Discussionmentioning
confidence: 99%